2012
DOI: 10.1093/pcp/pcs146
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a Basal Transcription Factor 3-Like Gene Osj10gBTF3 in Rice Results in Significant Plant Miniaturization and Typical Pollen Abortion

Abstract: BTF3, which was originally recognized as a basal transcription factor, has been known to be involved in transcription initiation, translational regulation and protein localization in many eukaryotic organisms. However, its function remains largely unknown in plant species. In the present study, we analyzed a BTF3-related sequence in Oryza sativa L. subsp. japonica, which shares the conserved domain of a nascent polypeptide-associated complex with human BTF3, and was referred to as Osj10gBTF3. The expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 80 publications
4
43
0
Order By: Relevance
“…RNAs extractions, the full length of cDNA synthesis, were carried out using the BTF3 gene-specific primers via procedures as described by Wang et al [6]. The amplified products of cDNA were cloned into a pMD18-T vector (TaKaRa).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNAs extractions, the full length of cDNA synthesis, were carried out using the BTF3 gene-specific primers via procedures as described by Wang et al [6]. The amplified products of cDNA were cloned into a pMD18-T vector (TaKaRa).…”
Section: Methodsmentioning
confidence: 99%
“…The amplified products of cDNA were cloned into a pMD18-T vector (TaKaRa). RNAi repression vector was constructed as suggested by Wang et al [6]. The resultant vector was incorporated into the EHA105 ( A. tumefaciens strain), which was used to infect rice embryogenic calli raised from mature seeds of Nipponbare to produce transformed calli.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding meshes well with the results from our study, in that this gene's expression peaked at stage 4 (in the middle of the seedling cotyledon's functional transition from yellow storage organ to green photosynthesizing organ), with the protein increasing dramatically in abundance coincident with the greening of the seedling cotyledon. Other studies have suggested that BTF3 has roles in biotic and abiotic stress response and pollen development (Huh et al, 2012;Wang et al, 2012;Kang et al, 2013).…”
Section: The Zinc Finger Gata Protein Is Found At Appreciable Levels mentioning
confidence: 98%